Efecto de la variación de la carga viva sobre el desempeño sísmico de edificios regular en altura y en planta. - Román-Bermúdez, Jesús Antonio (Instituto Tecnológico de Costa Rica, 2018)
The following project deals with the effects caused by variations in load in regular buildings in height and in plan. You can learn about the basic concepts of structural dynamics to apply in works of different kinds; In addition, it can observe the effects caused in the period of a structure when varying the load in different points in the height. You can observe the effects of three different earthquakes through the accelerogram obtained in each event, the earthquakes are Alajuela, Limón and Cinchona; Initially a response spectrum of the CSCR was used with an S4 and Seismic Zone 4 (it is the most critical condition) and finally the ductility suffered by the elements when the load is varied. For the execution of these effects two structures of 10 and 15 levels respectively were modeled in reinforced concrete with cutting walls; obtaining the drifts by means of the calculations mentioned in the seismic code of Costa Rica. We analyzed frames with the maximum load that typifies the CSCR for offices (for common use is considered 650 kg / m2) against the load of a mobile archive that is sold in the local market (1 T/m2). It is concluded that if we do not consider the loading of these files where it is going to be installed can cause alterations in dynamic structure behavior.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2018.
Keywords: Sismos; Dinámica; Estructura; CSCR; Análisis; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture::Building manufacturing engineering